Ambiguity in Defining Knowledge in Strategic Management - Mesjasz, Czesław; Szarucki, Marek (Studia Oeconomica Posnaniensia, 2019)
Defining knowledge in management is always associated with simplifications, beginning from an a priori approach - everybody knows what is knowledge through more or less reasonable qualitative interpretations and ending with attempts of operationalization. Definitional problems are derived from an implicit hierarchical structure of knowledge - knowledge about knowledge....ad infinitumand from fundamental paradoxes of knowledge, associated with its self-reflexive and self-referential character. These problems are especially important in strategic management. A deepened survey of literature in that area shows that the interpretations of knowledge in strategic management are simplified and inadequate to the needs of practice and theory. The aim of this paper is to primarily identify specific characteristics of the knowledge that is necessary in strategic management. Two supporting aims are proposed. First, identification of reasons for a limited number of analyses of the specificity of knowledge applicable in strategic management. Second, the development of a preliminary survey of characteristics of that type of knowledge.